(untitled) (Czech Journal of International Relations, 2024)
The transformation of the German armed forces is one of the topics of the current security policy of Germany. The position of the German armed forces has deteriorated in recent years when compared to the situation that existed several decades ago. This fact is reflected in such things as the growth of difficulties with recruitment, increase in the number of young people preferring civilian service to military service accompanied by the growth of the positive evaluation of civilian service, and in particular in dwindling financial resources of Bundeswehr. Despite these tendencies, Bundeswehr is not as yet perceived by German society as an institution a priory incompatible with democracy. The analysis of the reform of German armed forces shows that that the changes in this institution are taking place against the background of trends generating the "revolution in military affairs", even though, naturally, within the boundaries given by the Bundeswehr’s limited access to the resources of German society. The German armed forces of the future should be more mobile, with improved capability for strategic lift and strategic reconnaissance, more flexible organisational structure and command, better signals and communication equipment, and better equipment for automated command. The improvements of the German armed forces are aimed at areas that can help them to increase their effectiveness in missions taking place outside of the territory of Germany, while the capabilities that were in the focus in the past, i.e. the high intensity warfare capability in the battlefield of Central Europe, are currently being scaled down. The only specificity of the reform of the German armed forces in comparison with the reforms taking place in other European countries is the continuation of universal conscription, probably due to the belief of German political - and partly also military - elites that universal conscription has democratising effects.